Disputes over contemporary slave labor in Brazil and the precarization of the protective system - Sousa, Iury Alves de; Giesta Cabral, Rafael Lamera (Revista Chilena de Derecho del Trabajo y de la Seguridad Social, 2020)
The article analyzed the conceptual disputes over the extent of contemporary slave labor in Brazil to illustrate the growing abusive trend that violates both national and international guidelines on the protection of decent work. Focusing on the analysis of legislative disputes in the Brazilian parliament, it concludes that constitutional flexibilizations on the concept of contemporary slave labour amplify the vulnerability of workers within the protective system.